Pengaruh Agama terhadap Konstitusi: Studi Komparasi Lembaga Konstitusi Negara Iran dan Indonesia - Erlina, Fatni (Matan : Journal of Islam and Muslim Society; Vol 3 No 2 (2021): Matan: Journal of Islam and Muslim Society Vol 3 (No 2) 2021, 2021)
This paper aims to find out the differences and similarities in the roles and positions of constitutional institutions between Iran and Indonesia. Several Islamic countries have succeeded in finding a harmonious form in elaborating between religion and democracy which is marked by the existence of a constitution. Conflicts between religion and democracy often occur in the preparation of the state administration sistem. Iran and Indonesia are both pioneers of the existence of a constitutional institution to ensure the enactment of the constitution as a basic agreement for all citizens and the government of a country. So it is important to know how the political commitment of a country in ensuring all power runs within constitutive boundaries. This research is a literature research, through normative juridical and socio-historical approaches, the data are then analyzed descriptively and comparatively. The results of the study show that the role and position of the constitutional institutions between Iran and Indonesia have a number of similarities and differences. This is due to the background of the cultural and religious patterns.